Spatio-Temporal Windowing for Encoding Perceptually Salient Early Reflections in Parametric Spatial Audio Rendering - Jüterbock, Tobias; Brinkmann, Fabian; Gamper, Hannes; Raghuvanshi, Nikunj; Weinzierl, Stefan (Journal of the Audio Engineering Society, 2023)
Parametric spatial audio rendering aims to provide perceptually convincing audio cues that are agnostic to the playback system to enable the acoustic design of games and virtual reality. The authors propose an algorithm for detecting perceptually important reflections from spatial room impulse responses. First, a parametric representation of the sound field is derived based on perceptually motivated spatio-temporal windowing, followed by a second step that estimates the perceptual salience of the detected reflections by means of a masking threshold. In this work, a vertical dependency is incorporated into both these components. This was inspired by recent research revealing that two sound sources in the median plane can evoke two independent auditory events if their spatial separation is sufficiently large. The proposed algorithm is evaluated in nine simulated shoebox rooms with a wide range of sizes and reverberation times. Evaluation results show improved selection of early reflections by accounting for source elevation and suggest that for speech signals, the perceptual quality increases with an increasing number of rendered early reflections.